Analisis Pengaruh Gaji dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening pada Coffee Shop Kocoba Medan - Audri Tarigan; Yeni Absah; Nismah Panjaitan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of salary and work environment on employee performance, with job satisfaction as an intervening variable, at Coffee Shop Kocoba Medan. A quantitative approach was employed, with data collected through questionnaires from 35 respondents who are employees of Coffee Shop Kocoba. The data analysis technique used was Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results show that salary and work environment directly have a positive and significant effect on employee performance. Furthermore, job satisfaction was proven to be an intervening variable that strengthens the relationship between salary and work environment on employee performance. Salary factors, including timely payment and incentives, and a conducive work environment, both physically and non-physically, play a crucial role in improving employee satisfaction and productivity. This research is expected to serve as a reference for the management of Coffee Shop Kocoba in designing more effective human resource policies, particularly regarding salary provision, work environment improvement, and job satisfaction enhancement.